In planta Activity of Novel Copper(II)-Based Formulations to Inhibit the Esca-Associated Fungus Phaeoacremonium minimum in Grapevine Propagation Material - Battiston, Enrico; Compant, Stéphane; Antonielli, Livio; Mondello, Vincenzo; Clément, Christophe; Simoni, Andrea; Di Marco, Stefano; Mugnai, Laura; Fontaine, Florence (Frontiers in Plant Science, 2021)
Grapevine trunk diseases (GTD) are a serious and growing threat to vineyards worldwide. The need for innovative control tools persists since pesticides used against some GTDs have been banned and only methods to prevent infections or to reduce foliar symptoms have been developed so far. In this context, the application of imaging methods, already applied to study plant-microbe interactions, represents an interesting approach to understand the effect of experimental treatments applied to reduce fungal colonization, on GTD-related pathogens activity. To this aim trials were carried out to evaluate the efficacy of copper-based treatments, formulated with hydroxyapatite (HA) as co-adjuvant with innovative delivery properties, loaded with two different copper(II) compounds (tribasic sulfate and sulfate pentahydrate), applied to grapevine propagation material to inhibit fungal wood colonization. The treated rootstock and scion cuttings (Vitis vinifera L., Chardonnay) had been inoculated with a strain of Phaeoacremonium minimum (Pmi) compared to uninoculated rootstocks. Experimental treatments were applied during the water soaking process, comparing the copper(II) compounds pure or formulated with HA, to hydrate the cuttings. After callusing, grafted vines were grown under greenhouse conditions in a nursery and inoculated with Pmi::gfp7 or with Pmi wild-type. Fifteen weeks post-inoculation, woody tissues close to the inoculation site were sampled to evaluate efficiency of the treatments by studying the plant-microbe interaction by confocal laser scanner microscopy (CLSM). Copper and further elements were also quantified in the same tissues immediately after the treatments and on the CLSM samples. Finally, the grapevine defense responses were studied in the leaves of cuttings treated with the same formulations. The present investigation confirmed the relevant interaction of Pmi and the related transformed strain on the vascular tissues of grafted vines. Furthermore, in vitro assay revealed (i) the fungistatic effect of HA and the reduced effect of Cu fungicide when combined with HA. In planta assays showed (ii) the reduction of Pmi infection in propagation material treated with HA-Cu formulations, (iii) the movement of HA-Cu formulations inside the plant tissues and their persistence over time and (iv) the plant defense reaction following the treatment with pure HA or Cu, or combined.